2019
DOI: 10.3390/su11246905
|View full text |Cite
|
Sign up to set email alerts
|

A Building Retrofit and Sensitivity Analysis in an Automatically Calibrated Model Considering the Urban Heat Island Effect in Abu Dhabi, UAE

Abstract: Villas are a very common building typology in Abu Dhabi. Due to its preponderance in residential areas, studying how to effectively reduce energy demand for this type of building is critical for Abu Dhabi, and many similar cities in the region. This study aims to show the impact of proposed energy efficiency measures on a villa using a calibrated model and to demonstrate that to be accurate, the model must be driven using urban weather data instead of rural weather data due to the significance of the urban hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…), HVAC system, lighting, and operational schedules. A recent paper dealing with building retrofit and sensitivity analysis in Abu Dhabi (UAE) reported that the optimal strategies for given a case study villa are a cool roof, cool wall, seasonal energy efficiency ratio (SEER), and atrium shades, which may lead to total energy savings of 25% [27]. Abdullah and Alibaba reported that an integration of photovoltaics as responsive shading devices as a retrofit strategy for an energy-efficient office building would have a huge impact on energy savings.…”
Section: Building Retrofittingmentioning
confidence: 99%
“…), HVAC system, lighting, and operational schedules. A recent paper dealing with building retrofit and sensitivity analysis in Abu Dhabi (UAE) reported that the optimal strategies for given a case study villa are a cool roof, cool wall, seasonal energy efficiency ratio (SEER), and atrium shades, which may lead to total energy savings of 25% [27]. Abdullah and Alibaba reported that an integration of photovoltaics as responsive shading devices as a retrofit strategy for an energy-efficient office building would have a huge impact on energy savings.…”
Section: Building Retrofittingmentioning
confidence: 99%
“…An additional 1% of the LCE demand was added to represent the energy associated with end-of-life demolition and disposal (DDE). Because operational energy (OPE) was not the focus of this study, secondary data (Abu-Hijleh and Jaheen, 2019; AlQubaisi and Al-Alili, 2018; Bande et al. , 2019; Giusti and Almoosawi, 2017), was used to approximate the operational energy, as explained in a previous study (Rauf et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, the social context of the country is different from most countries; of the 9.3 million residents of the UAE, about 80% are foreigners from over 200 countries of the world. Population growth, urbanization and industrialization in the UAE have led to the challenge of rising energy demands over the past few decades [17,18]. In addition, urbanization, economic growth and financial development increase residents' purchasing power [19].…”
Section: The Study Contextmentioning
confidence: 99%